Pengembangan Variasi Latihan Pukulan Forehand Overhead Clear Bulutangkis Menggunakan Media Tutorial Atlet Pemula Badminton Teratai Club Medan - Al Farhans, Muhammad Fadlin; Sinulingga, Albadi; Mesnan, Mesnan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to create and develop variations of forehand overhead clear shot training in badminton games. The research problem is the athlete's ability to perform forehand overhead clear shots still looks poor. This research was conducted in the age group of 10-15 years old beginner athletes Badminton Teratai Club Medan. In this study using the type of R&D research refers to the development model of Borg and Gall. The subjects in this study were beginner athletes. the product in this study has been designed and then validated by 2 experts, namely, Sports Experts and Expert Practitioners. The small group test results of 89.12% were categorised as ‘Feasible’ and the large group test results of 85.89% were categorised as ‘Feasible’. Conclusion, this research produces a product in the form of a variation of forehand overhead clear shot training using media tutorials for beginner athletes of Badminton Teratai Club Medan. Keywords : Badminton Training, Forehand, Overhead Clear